Case Report on a Supracondylar Process of the Humerus: Morphological and Morphometric analysis - Aragão, José Aderval; Prado, Marcelo Lucas de Lima; Sant’Anna Aragão, Iapunira Catarina; Sant’Anna Aragão, Felipe Matheus; Reis, Francisco Prado; Mendonça, Deise Maria Furtado de (Brazilian Journal of Case Reports, 2024)
The supracondylar process is a rare anatomical variation characterized by an irregular bone prominence with a variable size. Found in the anteromedial part of the distal region of the humerus, can compress the median nerve and other structures. The aim of this paper was to perform a morphological and morphometric evaluation of this variation in a right dry humerus. Faces, margins, and shape of the process were observed. Measurements was taken from the process and the entire bone. The apex of the process points toward the transition between the trochlea and the humeral capitulum. The bony spicule was 6.24 mm long. The base of the spicule measured 6.80 mm in length and 4.18 mm in width. Longitudinal crests associated with the base of the process and a deep longitudinal depression were observed. The combined longitudinal length of the caudal and cranial crests together was 32.37 mm. The distance from the bone spicule to the medial epicondyle was 65.29 mm. In pathological cases, vascular disturbances, sensory deficits, and decreased muscle strength can be observed. A comprehensive description of this variation is crucial for enhancing current knowledge and awareness in clinical practice, as it aids in accurate diagnosis and treatment.